(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study examines the impact of rationality and experience on users’ decision to reapply for a digital peer-to-peer (P2P) loan, with behavioral intention as an intermediary factor, in the context of Yogyakarta, Indonesia. As the popularity of digital lending platforms increases, understanding the behavioral factors behind loan reapplication decisions is crucial. This study uses quantitative methods with Structural Equation Models (SEM), with data collected from active P2P users who have previously reapplied for a loan. Findings show that both rationality and experience significantly affect behavioral intention rates, which in turn affect reapplication behavior. Behavioral intention plays a crucial mediating role, linking cognitive and experiential factors to the decision to reapply for a loan. These results highlight the importance of cognitive evaluation and experiential memory in shaping financial behavior in the digital context, providing insights for financial technology providers, regulators, and educators.